From Fear to Fluency: Transforming Arabic Language Anxiety through Innovative Coping Mechanisms - Amalia, Nahdiyah; Kholiq, Ilham Nur (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This research aims to implement coping strategies to address anxiety in Arabic language at MA Al Amiriyah Banyuwangi. The research method uses a qualitative approach with a case study type, where data is collected through interviews, observations, and documentation. The research informants include the principal, the Curriculum Deputy, Arabic language teachers, and students. The research results show that coping strategies such as creating a supportive environment, using active learning methods, providing positive feedback, and using visual media are effective in reducing anxiety in learning Arabic. The conclusion of this research is that a holistic and collaborative approach, involving all stakeholders, is the key to creating an inclusive and effective learning environment to address Arabic language anxiety.